Application, comparative study, and multi-objective optimization of a hydrogen liquefaction system utilizing either ORC or an absorption power cycle. (22nd July 2022) - Cao, Yan; Dhahad, Hayder A.; Togun, Hussein; Aly, Ayman A.; Felemban, Bassem F.; El-Shafay, A.S.; Rashidi, Shima; Farhang, Babak
Abstract: Environmental degradation and global warming are presently two of the most pressing global concerns. According to the (IAE), around 80% of global energy demand has been met by fossil fuels in recent years, resulting in an increase in CO2 emissions as the primary greenhouse gas. Switching to renewable energy sources and using more energy-efficient energy systems are vital for mitigating environmental challenges and reducing our reliance on fossil fuels, among other things. Hydrogen fuels are primary renewable resources because of their reduced cost and ability to produce net-zero CO2 emissions. In the present study, a system is designed to generate power and liquid hydrogen from geothermal sources. The generated power by employing either the organic Rankin cycle (ORC) or absorption power cycle (APC) is compared to seek the best cycle performance from power generation standpoint. A comprehensive thermodynamic and economic modeling is carried out for the proposed system. In addition, a parametric study is applied to see which parameters affect the performance of the system. Multi-objective optimization is carried out to find the best operating point of the hydrogen liquefaction energy system. The system demonstrates better performance when APC is applied for power generation. The cost of generated liquid hydrogen by ORC and APC is 3.8 $/kg.LH2 and 3.6 $/kg.LH2, respectively. Furthermore, 0.014 $/kWh of electricity cost is reached by ORC compared to 0.012 $/kWh of APC. Parametric analysis shows that the higher the temperature and flow rate of the brine of geothermal fluid, the higher the efficiency and the lower cost. Finally, the multi-objective optimization pinpoints that the system's efficiency and unit product cost at the optimal ORC-based design is 33.85% and 0.0121 $/kWh. In comparison, the APC demonstrates better performance by 34.5% and 0.011 $/kWh. Highlights: Two cycles are proposed for simultaneous generation of power and liquid hydrogen. Comprehensive 3E analysis and multi-objective optimization is conducted. Effect of key design variables is foreseen for most liquid hydrogen generation. The superiority of APC-based system to the common ORC based system is pinpointed. It is found that scenario "b" has, more exergetic efficiency and lower LCOP of 1.92% and 10%, respectively.